Analysis of Participation in Maintaining Environmental Cleanliness through Ecological Intelligence - Nur Intan Permatasari; Oding Sunardi; Lufty Hari Susanto (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2021)
This research is a sequential explanatory mixed method research which consists of a quantitative research and a qualitative research. This study consists of two variables, the independent variable (X) namely Ecological Intelligence and the dependent variable (Y) namely Participation in maintaining Environmental Cleanliness. This study aims to obtain information about relationship between ecological intelligence and participation in maintaining environmental cleanliness and to find out other factors related to participation in maintaining environmental cleanliness of high school students in Cibinong. This research was conducted at SMA Negeri 2 Cibinong and SMA Negeri 3 Cibinong in the 2020/2021 academic year. The research began in November 2020 until June 2021. The subjects of this study are students of class XI MIPA at SMA Negeri 2 Cibinong and SMA Negeri 3 Cibinong. The research population was taken using a multistage random sampling technique. The research sample was determined by proportional random sampling technique using the slovin formula. Based on the calculation of the slovin formula, the number of samples was 166 students. The instrument used in this study is a non-test instrument, namely a questionnaire. The results of the study found that there was a positive relationship between ecological intelligence and participation in maintaining environmental cleanliness in SMA Negeri students in Cibinong District. The positive relationship is shown by the regression equation Ã = 32.524 + 0.673x with an r value of 0.697 and a coefficient of determination (r2) of 0.485, which means that 48.5% of ecological intelligence contributes to participation in maintaining environmental cleanliness, while the remaining 51.5% is a contribution from other factors beyond ecological intelligence. As for other factors related to participation in maintaining environmental cleanliness, namely: self-awareness, environment (family, friends, school), regulations, and information media. Keywords: Ecological intelligence, participation in maintaining enviromental cleanliness, student.